2010
DOI: 10.1097/cad.0b013e32833c2cf7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free fatty acids and lysolipids on cellular uptake of doxorubicin in human breast cancer cell lines

Abstract: Several fatty acids and lysolipids have been shown earlier to increase the permeability of membranes of artificial liposomes, thereby increasing the release of drugs such as doxorubicin (Dox) contained within them. Free fatty acids can also inhibit cancer cell growth in vitro, and it has been suggested that this inhibition results from increased membrane permeability. Clearly, therefore, increased membrane permeability could be used in the design of liposomes for targeted drug delivery. For example, as free fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…When integrating into the lipid bilayer, the fatty acid increases the curvature stress which leads to more leaky membranes. A similar behavior has been found for a wide range of saturated and unsaturated fatty acids as well as lysolipids which have the opposite sense of curvature ( P <1) 39, 67–73. Lysolipids also promote drug release, although less dramatically, probably because they are more water soluble compared to a fatty acid with the same acyl chain.…”
Section: The Powerful Language Of Shapesupporting
confidence: 68%
“…When integrating into the lipid bilayer, the fatty acid increases the curvature stress which leads to more leaky membranes. A similar behavior has been found for a wide range of saturated and unsaturated fatty acids as well as lysolipids which have the opposite sense of curvature ( P <1) 39, 67–73. Lysolipids also promote drug release, although less dramatically, probably because they are more water soluble compared to a fatty acid with the same acyl chain.…”
Section: The Powerful Language Of Shapesupporting
confidence: 68%
“…An increase in cell membrane permeability would provide more chances for anti-cancer elements to pass though the cell membrane and maybe even intra-cellular membranes, such as the mitochondrial membrane (Rasmussen et al, 2010). The detection of cell membrane permeability indicated that HUVEC and LoVo had similar tendencies with additional LA, though the membrane permeability of the low concentration treatment was much higher than that of the high concentration treatment within the same group.…”
Section: Discussionmentioning
confidence: 93%
“…Loss of membrane integrity is one of the earliest indicators of cell damage and a sign of serious injury. It leads to cell death [30] most probably due to changes in the permeability and fluidity of the cell membrane as well as changes in cellular uptake and intracellular metabolism, shown to occur within hours [31]. In the present report we provide evidence that in vitro chemosensitivity testing of CETC using propidium iodide uptake, which results in nuclear red fluorescence, allows assessment, before treatment, of whether the tumor cells will be sensitive to the intended drugs.…”
Section: Introductionmentioning
confidence: 60%
“…So far, chemosensitivity testing has only been performed in cell cultures derived from primary tumors or cell lines [30,31], using methods such as proliferation assays and in vitro clonogenic assays, microfluidic approaches and multidrug resistance assays [32][33][34][35][36], cell metabolic activity assays [37][38][39], molecular assays to monitor expression of markers for responsiveness [40], and in vivo imaging assays [41]. These approaches, however, all have major drawbacks.…”
Section: Discussionmentioning
confidence: 99%